2017
DOI: 10.2174/1566524017666170220103731
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants for STIM1 Activation During Store- Operated Ca2+ Entry

Abstract: Background STIM/ORAI-mediated store-operated Ca2+ entry (SOCE) mediates a myriad of Ca2+-dependent cellular activities in mammals. Genetic defects in STIM1/ORAI1 lead to devastating severe combined immunodeficiency; whereas gain-of-function mutations in STIM1/ORAI1 are intimately associated with tubular aggregate myopathy. At molecular level, a decrease in the Ca2+ concentrations within the lumen of endoplasmic reticulum (ER) initiates multimerization of the STIM1 luminal domain to switch on the STIM1 cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…Our model is fully compatible with the findings and conclusions of the Ma study in that the reorientation of the TM segments is a key step in the early activation cascade. A more recent study from the Zhou laboratory also reached similar conclusions (Ma et al, 2017). Jing et al has identified an additional player in the control of the CC1 domain SOAR interaction.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Our model is fully compatible with the findings and conclusions of the Ma study in that the reorientation of the TM segments is a key step in the early activation cascade. A more recent study from the Zhou laboratory also reached similar conclusions (Ma et al, 2017). Jing et al has identified an additional player in the control of the CC1 domain SOAR interaction.…”
Section: Discussionsupporting
confidence: 54%
“…They discovered that an ER-resident multipass transmembrane molecule they named STIMATE (also known as TMEM110) can also interact with the CC1 domain to weaken its interaction with SOAR (Jing et al, 2015). Although STIMATE appears to be an important modifier of the STIM1 activation process, it probably does not significantly change the conclusions of our study and those of Ma et al (Ma et al, 2015(Ma et al, , 2017.…”
Section: Discussionmentioning
confidence: 40%
“…Optogenetic mimicry of CC1-SOAR mediated autoinhibition. The interaction between CC1 and SOAR is required for STIM1 autoinhibition and to keep STIM1 inactive at the resting state 14,26,27 . We confirmed this by splitting the full-length STIM1 into two components at position 342, and appended each part with a different fluorescent protein tag ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…FRET measurements were recorded and analyzed with procedures similar to those described earlier [ 26 ]. Briefly, fluorescence imaging experiments were carried out using a ZEISS observer-Z1 microscope equipped with X-Cite® 120-Q (Lumen dynamics) light source, Semrock Bright Line filter sets (CFP (438 ± 12 Ex /482 ± 16 Em ), YFP (500 ± 12 Ex /542 ± 13.5 Em ), FRET raw (438 ± 12 Ex /542 ± 13.5 Em ), × 40 oil objective (N.A.…”
Section: Methodsmentioning
confidence: 99%